2003
DOI: 10.1007/s00296-003-0396-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of GaAs laser therapy on cervical myofascial pain syndrome

Abstract: Low-energy laser therapy has been applied in several rheumatoid and soft tissue disorders with varying rates of success. The objective of our study was to investigate the effect of laser therapy on cervical myofascial pain syndrome with a placebo-controlled double-blind prospective study model. It was performed with a total of 53 patients (35 females and 18 males) with cervical myofascial pain syndrome. In group 1 (n = 23), GaAs laser treatment was applied over three trigger points bilaterally and also one poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 18 publications
1
49
1
13
Order By: Relevance
“…Beneficial effects have been shown in a number of clinical trials adopting this approach [54,56,90] while others failed to reveal any successful effects [91,92]. However, in the latter two studies, no treatment parameters details and/or poor treatment parameters were evident.…”
Section: Contact Approachmentioning
confidence: 95%
“…Beneficial effects have been shown in a number of clinical trials adopting this approach [54,56,90] while others failed to reveal any successful effects [91,92]. However, in the latter two studies, no treatment parameters details and/or poor treatment parameters were evident.…”
Section: Contact Approachmentioning
confidence: 95%
“…레이저 치료는 치료횟수가 1∼15회였고, 10회 수행한 연구가 3건 (33%) 47,49,50) 으로 가장 많았다. 1건 52) 을 제외한 모든 연구는 trigger points 혹은 tender points를 사용하였다 (Table 4).…”
Section: 비특이적 만성 목 통증의 침구치료 방법unclassified
“…The study of Altan et al (2005) and Dundar et al (2007) revealed that laser therapy had no superiority over placebo groups in treatment of patients with chronic MRS in the neck.…”
Section: Goodwin Et Al (1992)mentioning
confidence: 99%